Women Religious Crossing between Cloister and the World Nunneries in Europe and the Americas, ca. 1200-1700 - Pérez Vidal, Mercedes (Spirituality and Monasticism, East and West, 2022)
This volume is the product of a collaborative research program undertaken since 2014 by the Société d'Études Interdisciplinaires sur les Femmes au Moyen Âge et à la Renaissance (seifmar). This program has focused on various aspects of the relationship between women and the religious in Europe during the Middle Ages and the Early Modern era, as well as how this interaction expanded across the Atlantic. Studies dedicated to the impact of women on the social, intellectual, and religious affairs of their era have grown in popularity over the past few decades. Research on these issues, however, has not progressed in an altogether coherently. On the contrary, it has presented considerable discrepancies in context and geography, as well as in the various aspects, themes, and research angles that this exceptionally broad domain encompasses. Moreover, there has been a profound lack of dialogue between researchers. Evidence of a communication breakdown is threefold: spatial, between different countries, and between the two sides of the Atlantic; temporal, between specialists of different time periods, in particular between medievalists and early-modernists; and lastly what can be called a lack of intra/ interdisciplinary communication. The above- mentioned research program was designed to eschew these traditional limitations.